Associations Between Timeliness of Therapy and Clinical and Economic Outcomes Among Patients With Serious Infections Due to Gram-negative Bacteria (GNB): How Much Does Delayed Appropriate Therapy (DAT) Matter?. (4th October 2017) - Bonine, Nicole G; Berger, Ariel; Altincatal, Arman; Wang, Rosa; Bhagnani, Tarun; Gillard, Patrick; Lodise, Thomas
Abstract: Background: Patients with serious GNB infections who receive DAT have worse outcomes. Most studies that have examined this issue include both antibiotic-resistant and susceptible pathogens. It is difficult to assign causality as DAT is correlated with resistance, which is associated with poorer prognosis. Our objective was to assess association between DAT and outcomes among patients with GNB infection, stratified by antibiotic susceptibility status. Methods: Hospitalized adults between 7/2011–9/2014 were identified from Premier Hospital Database. Patients were diagnosed with complicated urinary tract infection, complicated intra-abdominal infection, hospital-associated pneumonia, or bloodstream infection, and had a positive culture for GNB from a site consistent with infection type (date of culture draw was index date). Patients were required to receive antibiotics on this date or ≤2 days after. Delayed therapy was defined as no receipt of an antibiotic with microbiologic activity during this period. Patients were stratified by antibiotic-resistant GNB (Third-generation cephalosporin-resistant Enterobacteriaceae, carbapenem‐resistant (CR) Enterobacteriaceae, CR Pseudomonas sp ., or multi‐drug-resistant Pseudomonas sp .) vs. antibiotic-susceptible GNB counterparts. Inverse probability weighting and multivariate regression analyses were used to estimate the association between DAT and outcomes. Logistic models were used for composite mortality (in-hospital death or discharge to hospice) and discharge to home. Generalized linear models were used for post-index duration of antibiotic therapy, hospital length of stay (LOS), and costs. Results: A total of 6, 055 resistant and 50, 302 susceptible infections were identified; 2, 800 and 16, 585, respectively, received DAT. In multivariate analyses, DAT was associated with worse outcomes, including a 20% increased risk of composite mortality and an approximate 70% increase in LOS and total costs, respectively. The relative impact of DAT was nearly identical by antibiotic-resistant status (Figure ). Conclusion: Our study indicates that DAT is independently associated with poorer outcomes in serious infections due to GNB, irrespective of resistance status. Disclosures: N. G. Bonine, Allergan plc: Employee, Salary. A. Berger, Allergan plc: Consultant, Consulting fee. R. Wang, Evidera: Employee, Salary. T. Bhagnani, Allergan plc: Consultant, Consulting fee. P. Gillard, Allergan plc: Employee, Salary. T. Lodise, Allergan plc: Consultant and Scientific Advisor, Consulting fee and Speaker honorarium.